The Indonesian Socialist Party (PSI) 1950-1959: Political Role and Progress during Liberal Democracy - Armedyestu Priyonggo; Yety Rochwulaningsih; Indriyanto Indriyanto (Indonesian Historical Studies, 2018)
The establishment of PSI was a continuation of the movement of youth groups during the period of the National Movement which the members came from intellectual elites named PNI Baru. This organization had an important role in the form of Parliamentary Democracy system in Indonesia. During the independence period, PNI Baru became a political party called Partai Rakyat Sosialis (Paras), Paras then affiliated with Partai Sosialis Indonesia (Parsi) to become the Partai Sosialis in the late of 1945. Partai Sosialis appeared convincing as the dominating party in the course of Indonesian politics in early independence, placing Sjahrir and Amir as cabinet leaders for five consecutive periods. After the name of Partai Sosialis changed into PSI on February 12, 1948, the party was unable to be considered as a potential political party anymore. PSI had no chance to contribute to the political dynamics of Indonesia at that time. It was only after the recognition of Indonesian sovereignty that the PSI was able to carry out effective party work, including their involvement in cabinet in the 1950s. The PSI members were responsible of serving the government as ministers in the structure of the Natsir Cabinet of 1950, the Wilopo Cabinet of 1952 and Burhanuddin Harahap Cabinet of 1955, the other figures who had special affiliation and sympathy with PSI also became party representatives to serve the government during that period.